Strategic Management and Supply Chain Management in Organizational Theory Perspective: A Synergistic Approach - Naeem, Hafiz Muhammad; Hussain, Nazia Munazer (Archives of Business Research, 2015)
An ultimate question mark in history of strategic management is why and how organizations perform better than others? One comparative answer to explain this phenomena is an organization’s actions and strategic choices how it operate its supply chain. Supply chain management with the strategic management viewpoint is very fertile area and its integration can enrich this domain significantly. Network competition, hypercompetition and new competitive landscape got paramount significance in today’s competitive environment and strategy building process. The basic purpose of this literature review is to explain this shortcoming while explaining intended outcomes extracted from crucial abilities and configuration of supply chain management principles in hypercompetitive industries. While taking network competition, this report also extends the reference point of Abdulla (2009) on strategic demand network management (SDNM). Moreover this conceptual review will also develop a linkage in academic literature with respect to dynamic capabilities and supply chain management.